Comparison of undergraduate dental education in Aarhus, Brescia and Tromsø - Gangstøe, Anette Rognmo; Danielsen, Gøril Berg (UiT Norges arktiske universitet, 2018)
The aim of this work was to compare undergraduate dental educations at Aarhus University in Denmark, at the University of Brescia in Italy and at the University of Tromsø – The Arctic University of Norway and see if the students have different preconditions at graduation. Information about the curriculum and study subjects and oral health provision systems was collected from reports and articles. Observation was used as method when studying clinical teaching and patient treatment. In addition a number of students were interviewed regarding their opinions and experiences of their studies. Through our work we found out that the three different dental educations were rather similar as regards the theoretical contents in the education. There were also differences, especially when it comes to when the odontological subjects were introduced and how the clinic training was organized. The latter was related to the oral health care provision system in the country. At some of the schools the students felt that theoretical teaching and clinical practice were not very well synchronized. However, all the students felt their schools gave them a good undergraduate education and relevant clinical training. Every school had some interesting and useful ideas and practicalities that could be spread to other schools.